Post-Harvest Processing of Agricultural Products Supporting Local Wisdom in The 2022 Matching Fund Program - Ni Made Ayu Suardani Singapurwa; A.A. Made Semariyani; I Nyoman Rudianta; I Putu Candra; Sofia Utami Putri Sunarso; Grace Yohana Romauli Naibaho; Gusti Ngurah Oka Jiwantara (PT FORMOSA CENDEKIA GLOBAL, 2023)
Traditional food processing has promising potential for development, due to the high dependence of the community on processed meat and fish products to meet the nutritional needs of the community. The traditional food processing is very complex and is based more on the conception of local wisdom which has been passed down from generation to generation. The characteristics of traditional food processing are the type and quality of raw and additional materials which vary greatly, and environmental conditions that are difficult to control. The processing process still has many shortcomings because it relied more on natural factors, the treatment was not measured quantitatively and had not implemented a hygiene sanitation program.